The Unusual Surface Chlorophyll Signatures of Southern Ocean Eddies. Issue 9 (1st September 2018) - Dawson, H. R. S.; Strutton, P. G.; Gaube, P.
Abstract: Southern Ocean mesoscale eddies play an important role in ocean circulation and biogeochemical cycling, but their biological characteristics have not been well quantified at the basin scale. To address this, we combined a 15‐year tracked eddy data set with satellite observations of ocean color, sea surface temperature, and autonomous profiling floats to quantify the surface and subsurface properties of eddies. Anomalies of surface temperature and chlorophyll were examined in eddy‐centric composite averages constructed from thousands of eddies. Normalized surface chlorophyll anomalies (chlnorm ) vary seasonally and geographically. Cyclones typically show positive chlnorm, while anticyclones have negative chlnorm . The sign of chlnorm reverses during late summer and autumn for eddies between the Subtropical and Polar Fronts. The reversal is most obvious in the Indian sector, and we attribute this to a combination of eddy stirring (deformation of surface gradients by the rotational velocity of an eddy) and deeper winter mixing in anticyclones. Both chlnorm and sea surface temperature anomalies transition from dipole structures north of the Subtropical Front to monopole structures south of the Subantarctic Front. Sea surface temperature and chlnorm composites provide evidence for eddy trapping (transporting of anomalies) and eddy stirring. This research provides a basin‐scale study of surface chlorophyll in Southern Ocean eddies and reveals counterintuitive biogeochemical signals. Plain Language Summary: Ocean eddies are spinning parcels of water about 100 km across and 1, 500‐m deep. They occur everywhere in the ocean. In the Southern Hemisphere, eddies that spin clockwise are cooler than the surrounding ocean because their rotation causes cold, deep water to move upward. This upwelling brings nutrients essential for photosynthesis to the surface and makes clockwise‐rotating eddies more productive. Satellites can measure this productivity by sensing differences in ocean color, which result from the increased plankton. By analyzing thousands of Southern Ocean eddies, we found that in summer and autumn, eddies behave opposite to our expectations. That is, clockwise rotating eddies have lower plankton concentrations compared to neighboring waters and counterclockwise rotating eddies have higher concentrations. To explain this, we examined how deep these eddies mix the ocean in the preceding months. We found that counterclockwise rotating eddies mix the ocean deeper in winter, allowing more nutrients to enter their interiors, leading to higher productivity. This work is important because eddy productivity plays a significant role in the exchange of carbon between the ocean and the atmosphere. Carbon exchange in the Southern Ocean is thought to be changing, and this work helps explain an important piece of that process. Key Points: We quantify the seasonal and geographical variabilities in the physical and biological characteristics of Southern Ocean mesoscale eddies Atypical chlorophyll anomalies are observed in eddies between the Subtropical Front and the Polar Front during summer and autumn Eddy stirring, eddy trapping, and eddy pumping all contribute to physical and biological anomalies, depending on the region and season